THE EFFECTIVENESS OF MATHEMATICS TEACHING IN THE PROVINCES THAT HAVE MIGRATED DUE TO DISASTERS: A SURVEY STUDY - Korkmaz, Ebru; Taştepe, Mehtap (ISMAIL HAKKI MIRICI, 2023)
Due to the great disaster of February 6, 2023, known as the Kahramanmaraş earthquake, 11 provinces in Turkey were primarily affected. In these provinces, health, education, tourism and many other sectors were damaged. People living in the provinces with first-degree damage have settled in the nearest and less damaged provinces due to basic needs and education problems. In this regard, both the provinces that received in-migration and the people who migrated faced difficulties in various areas, especially in adaptation and transition. The purpose of this study is to obtain detailed information about the effectiveness of teaching mathematics in accordance with the difficulties of mathematics teachers in the provinces that migrated due to the earthquake. A total of 128 mathematics teachers were reached by the method of random sampling in the study designed in survey design. The instrument used to collect data is a questionnaire prepared by the researchers, which was set to 29 items based on expert opinions. The questionnaire was prepared using Google forms and data collection was started. Descriptive statistics were used for data analysis. The results showed that teachers indicated that they had no problems with lesson planning, lesson introduction, content presentation, and teaching, although they mostly reverted to traditional teaching, but they had difficulties in terms of motivating students for teaching, communicating with students, and measuring and evaluating. © 2014 by International Online Journal of Education and Teaching (IOJET).
Keywords: Earthquake; mathematics teaching; migration; questionnaire study